No progression of subclinical atherosclerosis in HIV-infected patients starting an initial regimen including tenofovir alafenamide/emtricitabine plus raltegravir, dolutegravir or elvitegravir/cobicistat during a two-year follow-up. Issue 4 (2nd April 2020) - Calza, Leonardo; Borderi, Marco; Colangeli, Vincenzo; Borioni, Aurora; Coladonato, Simona; Granozzi, Bianca; Viale, Pierluigi
Abstract: Objectives: Cardiovascular disease has become one of the most common comorbidities among HIV-infected patients, but available data about the correlation between antiretroviral drugs and progression rate of atherosclerotic disease are still limited. We evaluated the progression rate of carotid atherosclerosis in patients starting an initial antiretroviral regimen including one integrase strand transfer inhibitor (INSTI). Methods: Observational, prospective study involving HIV-1-infected, antiretroviral therapy-naive, adult patients who started an antiretroviral regimen including tenofovir alafenamide/emtricitabine (TAF/FTC) plus raltegravir (RAL group), elvitegravir/cobicistat (EVG/c group), or dolutegravir (DTG group). Patients with known cardiovascular disease or diabetes mellitus were excluded from the study. The progression rate of atherosclerosis has been assessed by carotid Doppler ultrasonography at baseline and after 24 months. Results: Overall, 102 patients were enrolled into the study: 73 males, with mean age of 48.7 years: 32, 36 and 34 patients were included in the RAL, EVG/c and DTG groups, respectively. The baseline features of the enrolled patients were comparable across the three groups. At 24 months, the mean intima-media thickness (IMT) increase at the carotid bifurcation was 0.026 mm in the RAL group, 0.029 mm in EVG/c group and 0.032 mm in DTG group. The mean IMT increases after 24 months were comparable across the three groups and statistically not significant in all the evaluated anatomical sites. Conclusions: The initial antiretroviral therapy with TAF/FTC plus RAL, EVG/c or DTG for 24 months led to a comparable and not significant effect on the progression rate of carotid atherosclerosis.